IDENTITAS DAN PERAN TOKOH DALAM LE MYSTÈRE DE LA CHAMBRE JAUNE KARYA GASTON LEROUX - Hawati Hamid, Kahimma; Bandu, Irianty (Universitas Hasanuddin, 2019)
This research aims to present a picture of three figures, describes the relationship of identity and the role of the three character depicted in the story, and describes the factors that cause a someone to change his identity and role. The theory used is the characterization theory by Shlomith Rimmon-Kenan, that is theory Direct definition and Indirect presentation, using twomethods approaches, that is intrisic and extrinsic. The conclusion of this research shows that the two main male figures changed their identity and role several times, while one female figure did not change her identity only in her changing role.